The Role of Fluids in Melting the Continental Crust and Generating Granitoids: An Overview - Jiahao Li; Xing Ding; Junfeng Liu (Geosciences, 2022)
Granite is a distinctive constituent part of the continental crust on Earth, the formation and evolution of which have long been hot research topics. In this paper, we reviewed the partial melting processes of crustal rocks without or with fluid assistance and summarized the role of fluids and volatiles involved in the formation of granitic melts. As a conventional model, granitoids were thought to be derived from the dehydration melting of hydrous minerals in crustal basement metamorphic rocks in the absence of external fluids. However, the external-fluid-assisted melting of crustal metamorphic rocks has recently been proposed to produce granitoids as extensive fluids could be active in the deep continental crust, especially in the subduction zones. It has been demonstrated experimentally that H2O plays a crucial role in the partial melting of crustal rocks, in which H2O can (1) significantly lower the solidus temperature of the melted rocks to facilitate partial melting; (2) affect the melting reaction process, mineral stability, and the composition of melt; and (3) help the melt to separate more easily from the source area and aggregate to form a large-scale magma chamber. More importantly, dissolved volatiles and salts in the crustal fluids could also lower the solidus temperature of rocks, affect the partitioning behaviors of trace elements between minerals and melts, and facilitate the formation of some distinctive granitoids (e.g., B-rich, F-rich, and high-K granitoids). Furthermore, various volatiles dissolved in fluids could result in elemental or isotopic fractionation as well as the diversity of mineralization during fluid-assisted melting. In-depth studies regarding the fluid-assisted partial melting of crustal rocks will facilitate a more comprehensive understanding of melting of the Earth’s crust, thus providing strong theoretical constraints on the genesis and mineralization of granitoids as well as the formation and evolution of the continental crust.